Acoustic doppler velocimeter backscatter for suspended sediment measurements: Effects of sediment size and attenuation. (January 2020) - Sahin, Cihan; Ozturk, Mehmet; Aydogan, Burak
Abstract: Use of backscatter output from a 10-MHz acoustic Doppler velocimeter (ADV) for quantifying suspended sediment concentration was investigated in a laboratory setting. The ADV was immersed in a 125-liter solid polycarbonate circulation tank in which known concentrations of non-cohesive quartz sediments (63–500 µm size range) were mixed in freshwater to obtain homogeneous solutions. Six different size fractions under a wide range of concentration conditions up to 10 kgm − 3 were used in the tests. Empirical relations between the acoustic backscatter strength and concentration for each sediment size fraction revealed that there are size-dependent upper and lower bounds on measurable concentrations. Above or below an optimum number of particles in suspension, the performance degrades due to insufficient scatterers which results in a lower bound, and high acoustic attenuation which results in an upper bound on concentration. Both upper and lower bounds increased with increasing sediment concentration, providing, in general, a wider applicability range for larger particles. The range of measurable conditions was broad enough to make the approach useful for sand sizes and concentrations commonly encountered in nature. Effect of sound attenuation was also examined in detail by correcting the acoustic backscatter for transmission losses due to spreading, absorption of energy by water and attenuation due to suspended sediments. The results showed that the effect of transmission losses varies significantly depending on sediment size and concentration, which especially becomes important at high concentrations. This is the first time this effect is quantified to show the direct impact of signal attenuation on suspended sediment measurements using an ADV.